ASME/STLE 2012 International Joint Tribology Conference 2012
DOI: 10.1115/ijtc2012-61088
|View full text |Cite
|
Sign up to set email alerts
|

Non-Iterative Finite Element Scheme for Combined Annular-Thrust Porous Aerostatic Bearings Analysis

Abstract: The key points of method derivation and a numerical example for bearing with three dimensional air flow are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Analysis is also done using the finitedifference method (Silveira et al, 2010;Majumdar, 1976) and the finite-element method [4,8] (Tian, 1998;Luong et al, 2004). Assuming one-dimensional flow in the porous bulk, the equation for the bulk can be integrated numerically, which reduces the dimension of the problem and, therefore, the computation time (Silveira et al, 2010;Tian, 1998;Loung et al, 2004;Khan and Hwang, 2012). Khan and Hwang (2012) developed a fast finite element scheme for analyzing porous aerostatic bearings and showed that the radial load-carrying capacity was limited by the pressure growth around the shaft.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis is also done using the finitedifference method (Silveira et al, 2010;Majumdar, 1976) and the finite-element method [4,8] (Tian, 1998;Luong et al, 2004). Assuming one-dimensional flow in the porous bulk, the equation for the bulk can be integrated numerically, which reduces the dimension of the problem and, therefore, the computation time (Silveira et al, 2010;Tian, 1998;Loung et al, 2004;Khan and Hwang, 2012). Khan and Hwang (2012) developed a fast finite element scheme for analyzing porous aerostatic bearings and showed that the radial load-carrying capacity was limited by the pressure growth around the shaft.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming one-dimensional flow in the porous bulk, the equation for the bulk can be integrated numerically, which reduces the dimension of the problem and, therefore, the computation time (Silveira et al, 2010;Tian, 1998;Loung et al, 2004;Khan and Hwang, 2012). Khan and Hwang (2012) developed a fast finite element scheme for analyzing porous aerostatic bearings and showed that the radial load-carrying capacity was limited by the pressure growth around the shaft. However, there has been no report on the effect of the arc on the annular-thrust to increase the load-carrying capacity.…”
Section: Introductionmentioning
confidence: 99%